Some Practical Matters Related to Riviera Soil, Depth to Clay, Water Table, Soil Organic Matter, and Swingle Citrumelo Root Systems - Bill Castle; Mace Bauer; Brian Boman; Tom Obreza (EDIS)
This document is Fact Sheet HS-894, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published December 2002.